Agroforestry rubber networks and farmers groups in Phatthalung area in Southern Thailand: A potential for an innovation platform? - Penot, Eric; Theriez, Marion; Michel, Isabelle; Tongkaemkaew, Uraiwan; Chambon, Benedicte (Forest and Society, 2022)
The study took place in southern Thailand, in Phatthalung province, and is part of “Heveadapt,” a Franco-Thai research project. The aim of this project was to show how smallholder rubber plantations can adapt and remain sustainable in the face of variable climatic conditions and deep changes in socio-economic context. Among the various types of cropping systems, agroforestry practices were identified as promising. Rubber agroforestry systems (AFS) are economically more productive than rubber monocrop plantations and give more flexibility to smallholders, in particular when rubber prices are low, which has been the case since 2013. However, adoption of AFS during the mature period of the plantations is very low in Thailand. The policy to boost rubber agroforestry practices still needs to be developed with all local stakeholders. The objectives of the study were to identify the possibilities and capacities to use current AFS dynamic networks as a basis to set up a rubber agroforestry innovation platform. The research team studied: i) farmers’ collective organizations, groups or networks with rubber AFS partially or entirely and ii) the social dynamic enabling the sharing of knowledge and know-how. An individual producer’s grid, with original farmers or strong knowledge with ease of sharing, was also studied. The role of local institutions involved in the promotion of rubber AFS was also analyzed. This allowed us to design an innovation platform and to define activities that suit the socio-economic context of Phatthalung province. The main aims of the platform are to promote cooperation among innovative producers and the transmission between them of knowledge and know-how about rubber AFS. This could an efficient tool that Thai rubber institutions could set up to encourage the adoption of rubber AFS by farmers.